Current status of checkpoint inhibitors in lymphoma. (September 2015) - Jamil, Muhammad Omer; Lohiya, Vipin; Mehta, Amitkumar
Cancer immunotherapy is evolving very fast. With understanding of tumor and immune system interactions, two pathways have been identified through which tumor cells evade and escape immune system. Blocking these pathways by monoclonal antibodies has shown promising results in wide variety of tumors. The treatment of lymphomas have been evolving with various new molecules ranging from monoclonal antibodies, antibody–drug conjugates to small molecule inhibitors. Here, we review the activity of immune checkpoint inhibitors in various lymphomas. These agents have shown very promising activity in Hodgkin lymphoma and other B-cell lymphomas in early-phase clinical trials.